Skrining Fitokimia dan Aktivitas Antiangiogenesis Ekstrak Etil Asetat Buah Galoba (Hornstedtia minor (Blume) Valeton) Terhadap Membran Korioalantois Embrio Ayam - Eva Feriadi; Wahyu Nuraini Hasmar; Dian Ayu Kusuma Ningrum; Muarifah Mukrimin Adam; Amira Hasmar (Jurnal Tumbuhan Obat Indonesia, 2025)
Angiogenesis is the process of new blood vessel formation that plays a crucial role in tumor growth andmetastasis by supplying oxygen and nutrients to cancer cells. Therefore, the inhibition of angiogenesis hasbecome a promising strategy in the development of natural product-based anticancer therapies. The genusHornstedtia has been reported to possess various biological activities; however, scientific informationregarding the species Hornstedtia minor (Blume) Valeton remains very limited. This study aimed to identifythe secondary metabolite constituents and evaluate the potential antiangiogenic activity of the ethyl acetateextract of H. minor (Blume) Valeton fruit. Extraction was carried out using the maceration method with ethylacetate as the solvent. Qualitative phytochemical screening was conducted to identify the classes of secondarymetabolites present in the extract. Antiangiogenic activity was evaluated using the Chorioallantoic Membrane(CAM) assay on 9-day-old chicken embryos with treatment groups consisting of a normal control, a negativecontrol, and extract concentrations of 1, 10, and 100 μg/mL. The main parameter observed was the percentageinhibition of blood vessel formation on the chorioallantoic membrane. Phytochemical screening revealed thepresence of several secondary metabolites, including alkaloids, flavonoids, terpenoids, and polyphenols. Theantiangiogenic assay demonstrated that the percentage of blood vessel inhibition increased with increasingextract concentration, with the highest inhibition activity reaching 98% at a concentration of 100 μg/mL.These findings indicate that the ethyl acetate extract of H. minor (Blume) Valeton fruit exhibits potentialantiangiogenic activity in the CAM model and may serve as a promising source of natural antiangiogeniccandidate agents, warranting further mechanistic studies and biological evaluations. Keywords: Galoba, Hornstedtia minor (Blume) Valeton, Phytochemical, Antiangiogenesis, CAM, Anticancer